Mengasah Kemampuan Imajinasi Anak Dengan Bermain Dan Belajar Di Panti Asuhan Muda Kartika Anak Indonesia - Ruth Angelica Angel; Malida Putri (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
The community service program is defined as the experience of science and technology carried out by universities in an institutional manner through scientific methods directly to the community. Community service carried out at the orphanage is a form of student service to provide useful knowledge for the surrounding community, especially at the orphanage. The author does a service at the Kartika Anak Indonesia Youth Orphanage with the specific aim of giving enthusiasm to hone children's imagination abilities. The main problem faced is children's time to play and learn. In addition to learning, children must also have time to play with friends, in order to train their social soul. Children's imagination abilities must also be developed so that they can think actively and creatively in all fields. Therefore, with this dedication the author intends to carry out a mini project at the orphanage by honing children's imagination abilities.